ChemInform Abstract: An Alkyne Diboration/6π‐Electrocyclization Strategy for the Synthesis of Pyridine Boronic Acid Derivatives. Issue 35 (August 2016) - Mora‐Rado, Helena; Bialy, Laurent; Czechtizky, Werngard; Mendez, Maria; Harrity, Joseph P. A.
Abstract: The novel diboration/6π‐electrocyclization strategy enables rapid access to bicyclic pyridines, although the suitability of this method to access monocyclic heterocycles will likely require further method development.